The Correlation Between Growth Mindset and Foreign Language Speaking Anxiety (FLSA) in Arabic Language Learning (A Study of Grade XII Religious Studies Student at Senior High School) - Jeannyta Eka Maulindah; Mahbub (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examined the relationship between growth mindset and foreign language speaking anxiety (FLSA) among Grade XII Religious Studies students at MAN 1 Banyuwangi. Using a quantitative correlational design, data were collected in 2025 from 37 students through Likert-scale questionnaires measuring growth mindset (based on Dweck’s theory) and FLSA (adapted from the Foreign Language Classroom Anxiety Scale). Data were analyzed using descriptive statistics and Pearson Product Moment correlation after meeting statistical assumptions. The results indicated that students demonstrated a moderate to high level of growth mindset and a moderate level of FLSA. Correlation analysis revealed a significant positive relationship with strong effect size (r = 0.720, p < 0.001), indicating that higher growth mindset was associated with higher speaking anxiety. This finding contrasts with dominant studies reporting negative correlations between the two variables. In this context, the positive association may reflect facilitative anxiety, suggesting that students with stronger developmental beliefs experience heightened performance awareness rather than debilitating fear. These findings highlight the contextual complexity of the relationship between growth mindset and language anxiety and suggest the importance of integrating cognitive and emotional support in foreign language instruction.